Covid-19 Pandemic and Volatility of Sugar Price at Regional Level in Indonesia for The Period August 2018-August 2021 - Meliany, Birka Septy; Sahara,; Probokawuryan, Mutiara; Ahmad, Fahmi Salam (Jurnal Manajemen dan Agribisnis, 2022)
It is expected that the COVID-19 pandemic provides a significant impact on food price volatility in many products including sugar. The paper aims to analyze the price dynamic of sugar before covid (1st August – 2nd March 2020) and during the covid outbreak (3rd March – 31th August 2021) in all provinces in Indonesia by using the t-test and ARCH GARCH model. Based on Augmented Dickey-Fuller analysis before and during covid, the prices of sugar in Indonesia were stationary at the “first difference”. The results reveal that the prices of sugar in all provinces in Indonesia before covid was lower compared to during the COVID-19 pandemic. According to ARCH GARCH results, sugar prices were much more volatile in Riau, Jambi, West Java, East Nusa Tenggara, West Kalimantan, South Sulawesi, Central Sulawesi, and West Papua. As such, the government should focus to reduce the price volatility of sugar in these provinces.Keywords: ARCH GARCH, COVID-19, sugar prices, stationarity, volatility